Comparing in person and internet methods to recruit low-SES populations for tobacco control policy research. (December 2019) - Greiner Safi, Amelia; Reyes, Carolyn; Jesch, Emma; Steinhardt, Joseph; Niederdeppe, Jeff; Skurka, Christofer; Kalaji, Motasem; Scolere, Leah; Byrne, Sahara
Abstract: Tobacco use and the associated consequences are much more prevalent among low-SES populations in the U.S. However, tobacco-based research often does not include these harder-to-reach populations. This paper compares the effectiveness and drawbacks of three methods of recruiting low-SES adult smokers in the Northeast. From a 5-year, [funding blinded] grant about impacts of graphic warning labels on tobacco products, three separate means of recruiting low-SES adult smokers emerged: 1) in person in the field with a mobile lab vehicle, 2) in person in the field with tablet computers, and 3) online via Amazon Mechanical Turk (MTurk). We compared each of these methods in terms of the resulting participant demographics and the "pros" and "cons" of each approach including quality control, logistics, cost, and engagement. Field-based methods (with a mobile lab or in person with a tablet) yielded a greater proportion of disadvantaged participants who could be biochemically verified as current smokers—45% of the field-based sample had an annual income of <10, 000 compared to 16% of the MTurk sample; 40–45% of the field-based sample did not complete high school compared to 2.6% of the MTurk sample. MTurk-based recruitment was substantially less expensive to operate (1/14th the cost of field-based methods) was faster, and involved less logistical coordination, though was unable to provide immediate biochemical verification of current smoking status. Both MTurk and field-based methods provide access to low-SES participants–the difference is the proportion and the degree of disadvantage. For research and interventions where either inclusion considerations or external validity with low-SES populations is critical, especially the most disadvantaged, our research supports the use of field-based methods. It also highlights the importance of adequate funding and time to enable the recruitment and participation of these harder-to-reach populations. Highlights: Web methods may inadequately involve those most impacted: low-SES populations. Field methods enable biochemical proof of smoking status; MTurk currently does not. Compared to MTurk, these field methods require more time, funding and coordination. Field methods can facilitate research participation by the most disadvantaged.